Quality cutting production of chrysanthemum (Dendranthema grandiflora) as influenced by integrated nutrient management of the plants during production phase - LAISHRAM, NOMITA; DHIMAN, S R; GUPTA, Y C; SINGH, ARVINDER; BHARDWAJ, S K (The Indian Journal of Agricultural Sciences, 2016)
This investigation was conducted at the Research Farm of Department of Floriculture and Landscaping, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Solan, Himachal Pradesh during the year 2010 and 2011 to ascertain the rooting behavior of cuttings taken from two chrysanthemum (Dendranthema grandiflora) cultivars Purnima and Ajay as affected by integrated nutrient management during the production phase of the plants. Plants grown under open field condition were subjected to 17 different nutritional regimes in a factorial Randomized Block Design (RBD) replicated thrice. After flowering was over, plants were headed back. Regenerated cuttings from headed back plants were studied for various parameters. The results revealed that plants receiving treatment comprising of 22.5 g/m2 each of NPK + Vermicompost (1 kg/m2) + Biofertilizers (Azotobacter + PSB + VAM) produced the maximum number of cuttings/plant (36.45), length of the longest root (8.58 cm), number of roots/plant (28.95), highest rooting percentage (95.52 %) and maximum fresh weight of cuttings at harvest (3.79 g) and after rooting (3.89 g). The same treatment also took the least number of days (25.20 days) for rooting to occur. Plants treated with 15 g/m2 each of NPK + Vermicompost (1 kg/m2) + Biofertilizers recorded the highest nitrogen contents of cuttings at harvest (5.09 %) and after rooting (4.64 %). Among the cultivars, Purnima exhibited maximum number of cuttings/plant (37.86), lesser number of days for rooting (20.97) and maximum nitrogen contents of cuttings at harvest (4.16 %) and after rooting (4.47 %), whereas cultivar Ajay recorded the maximum length of the root (6.38 cm) and number of roots/plant (22.46).